Chronic vertebrobasilar insufficiency in subclavian steal syndrome. Issue 3 (4th February 2021) - Phillips, Stephanie; Memon, Anza B.
Abstract: Subclavian steal syndrome is a vascular disorder that consists of significant blood supply restriction with resultant insufficiency of the vertebrobasilar artery and the subclavian artery causing symptomatic insufficiency to the brain and upper extremity. It is important to recognize this condition in patients with subacute to chronic posterior circulation vascular insufficiency as early diagnosis and treatment can have good clinical outcomes (J Clin Neurosci. 2010;17 :1339). CT angiogram of the head and neck should be considered in patients with chronic vertebrobasilar insufficiency to evaluate subclavian steal syndrome. Abstract : Subclavian steal syndrome is a vascular disorder that consists of significant blood supply restriction with resultant insufficiency of the vertebrobasilar artery and the subclavian artery causing symptomatic insufficiency to the brain and upper extremity. It is important to recognize this condition in patients with subacute to chronic posterior circulation vascular insufficiency as early diagnosis and treatment can have good clinical outcomes. CT angiogram of the head and neck should be considered in patients with chronic vertebrobasilar insufficiency to evaluate subclavian steal syndrome.